2014
DOI: 10.1371/journal.pone.0107161
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Exon 19 Deletion Were Associated with Longer Progression-Free Survival Compared to Those with L858R Mutation after First-Line EGFR-TKIs for Advanced Non-Small Cell Lung Cancer: A Meta-Analysis

Abstract: BackgroundsIt has been extensively proved that the efficacy of epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) is superior to that of cytotoxic chemotherapy in advanced non-small cell lung cancer (NSCLC) patients harboring sensitive EGFR mutations. However, the question of whether the efficacy of EGFR-TKIs differs between exon 19 deletion and exon 21 L858R mutation has not been yet statistically answered.MethodsSubgroup data on hazard ratio (HR) for progression-free survival (PFS) of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
128
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(144 citation statements)
references
References 41 publications
(53 reference statements)
7
128
2
Order By: Relevance
“…However, only 42 patients (39.6%) in this study received the EGFR-TKI treatment. Although the roles of the exon 19 deletion and exon 21 L858R mutation in EGFR mutation remain controversial, our results, which are in line with those of previous studies (29,30), show that NSCLC with exon 19 deletions or NSCLC with exon 21 L858R are two types of malignancies with different clinical characteristics and pathogenesis. The exact mechanisms for achieving satisfactory outcomes in exon 19 deletion remain unclear.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, only 42 patients (39.6%) in this study received the EGFR-TKI treatment. Although the roles of the exon 19 deletion and exon 21 L858R mutation in EGFR mutation remain controversial, our results, which are in line with those of previous studies (29,30), show that NSCLC with exon 19 deletions or NSCLC with exon 21 L858R are two types of malignancies with different clinical characteristics and pathogenesis. The exact mechanisms for achieving satisfactory outcomes in exon 19 deletion remain unclear.…”
Section: Discussionsupporting
confidence: 92%
“…The median CPFS time of those patients with exon 19 deletion was substantially increased to 12.0 months. In a meta-analysis (29), those patients with exon 19 deletion showed a longer PFS than those with exon 21 L858R mutations (HR =0.75, 95% CI, 0.65 to 0.85; P<0.001). Li et al (30) reviewed 106 NSCLC patients with brain metastasis from NSCLC.…”
Section: Discussionmentioning
confidence: 97%
“…Exon 19 has stronger bonds with TKI (gefitinib) than exon 21, leading to more dominant exon 21 pro-gressive diseases. The meta-analysis study by Zhang et al (2014) from 13 studies found that exon 19 had progression free survival longer than exon 21 in the administration of gefitinib as first line. Three hypo-theses had been developed today that exon 19 has greater affinity for EGF receptors than exon 21.…”
Section: Discussionmentioning
confidence: 99%
“…Three hypo-theses had been developed today that exon 19 has greater affinity for EGF receptors than exon 21. T790M, as a secondary mutation that is resistant to TKI, more commonly occurs with exon 21 L858R, which is a point mutation with the largest proportion of exon 21 and exon 18 (G719S) which more often appear along with exon 21 (L858R) (Zhang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation